2018
DOI: 10.1037/sgd0000252
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sexual satisfaction for partnered lesbian, gay, and bisexual adults.

Abstract: Past research on sexual satisfaction (SS) has primarily developed along three lines of research: interpersonal exchange as related to SS, impact of body image on sexuality and SS, and dysfunction and sexual anxiety as detractors from SS. Furthermore, past research has tended to focus on heterosexual couples, thereby excluding potentially important predictors of SS that are unique to LGB men and women. In this study, we sought to integrate the three disparate lines of research related to SS and attend to LGB-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 59 publications
1
15
0
1
Order By: Relevance
“…As for the LGBT community, little research exists, yet findings point in the same direction. Shepler et al (2018) found that sexual anxiety, relationship commitment, body image, and pride in identity significantly contribute to predicting sexual satisfaction in LGBT groups. Peplau et al (2009) compared body dissatisfaction and comfort with one’s body during sexual activity among the aforementioned groups.…”
Section: Introductionmentioning
confidence: 92%
“…As for the LGBT community, little research exists, yet findings point in the same direction. Shepler et al (2018) found that sexual anxiety, relationship commitment, body image, and pride in identity significantly contribute to predicting sexual satisfaction in LGBT groups. Peplau et al (2009) compared body dissatisfaction and comfort with one’s body during sexual activity among the aforementioned groups.…”
Section: Introductionmentioning
confidence: 92%
“…Most studies focused on sexual satisfaction have focused their interest on the Caucasian/ Anglo-Saxon heterosexual population [8][9][10], and research among the same-sex attracted population is Int. J. Environ.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, their body image experiences are likely influenced by the extent to which they identify with each of these communities and other identity-related communities (e.g., racial/ethnic groups). In a study of lesbian, gay, and bisexual men and women currently in a romantic relationship, Shepler et al (2018) considered identity pride and found a positive association between pride and sexual satisfaction. Identity-related factors such as sexual minority stress have been linked to poor body image outcomes in past research (e.g., Convertino et al, 2021; Mason et al, 2018; Miller & Luk, 2019; Watson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among the limited research regarding body image and relationship functioning in sexual minority couples, Shepler et al (2018) found body image (i.e., measured as satisfaction with one’s body) to be associated with one’s own sexual satisfaction, but not relationship commitment, in a sample of lesbian, gay, and bisexual men and women in relationships. Similarly, a study of 217 bisexual women in romantic relationships with men and women found body dissatisfaction and relationship satisfaction were negatively correlated (Kashubeck-West et al, 2018).…”
Section: Dyadic Associations Among Body Image and Relationship Factor...mentioning
confidence: 99%